Representações sociais e profissionais da saúde: saúde sexual e reprodutiva dos homens, masculinidades e infertilidade - Souza, Ana Flavia de (2022)
Men's sexual and reproductive health was consolidated by law in 2009 in Brazil, however, the discussion on the subject is still shy, both in academia and in people's daily lives, especially when it comes to infertility in men. There are still many taboos, myths and stereotypes hovering over the subject, because it circulates in the social imaginary that men should be strong, virile, reproductive. Considering that men's sexual and reproductive health issues, including infertility, involve, in addition to biological and medical issues, social, relational and environmental issues, we carried out a research during the master's degree in psychology, whose objective was to identify and understand the different representations that health professionals build on masculinities and infertility in men. In the third part, there is a study whose objective was to understand how social representations of masculinities constitute the practices of health professionals related to the problem of infertility in men. We carried out a qualitative research, with semi-structured interviews with 12 health professionals from the public and private network, who work with men's sexual and reproductive health in Rio Grande do Sul, Brazil (study 2). The results of study 1 indicate that: (a) infertility in men is still seen from a biological and medical point of view, crossed by different myths and stereotypes, (b) masculinities, in their different nuances, interfere in the construction of social representations about infertility in men and (c) there are barriers to accessing health services that are connected to representations of masculinity. Study 2 pointed to different representations of masculinity, including hegemonic and non-normative masculinities, and that infertility is still associated with women. The study also showed that there are problems in the physical structure, care provided and demand for sexual and reproductive health services by men, causing preventive health actions to not occur. The studies presented made it possible to respond to the research objectives and contributed to the understanding of a field of study that deserves attention, the sexual and reproductive health of men. The studies presented made it possible to respond to the research objectives and contributed to the understanding of a field of study that deserves attention, the sexual and reproductive health of men. Difficulties were encountered in carrying out study 2 resulting from the conditions imposed by the COVID-19 pandemic, which caused changes in the way the interviews were carried out. The research took place through online platforms, impacting the participants' adherence to the research. We suggest carrying out other review studies on the subject, considering other languages and countries, expanding reflections on the subject; similarly, empirical studies that can look at infertility through other audiences, such as men with infertility, or, also, studies with health professionals from other regions and locations.